Diet compositions and trophic guild structure of the eastern Chukchi Sea demersal fish community. (January 2017) - Whitehouse, George A.; Buckley, Troy W.; Danielson, Seth L.
Abstract: Fishes are an important link in Arctic marine food webs, connecting production of lower trophic levels to apex predators. We analyzed 1773 stomach samples from 39 fish species collected during a bottom trawl survey of the eastern Chukchi Sea in the summer of 2012. We used hierarchical cluster analysis of diet dissimilarities on 21 of the most well sampled species to identify four distinct trophic guilds: gammarid amphipod consumers, benthic invertebrate generalists, fish and shrimp consumers, and zooplankton consumers. The trophic guilds reflect dominant prey types in predator diets. We used constrained analysis of principal coordinates (CAP) to determine if variation within the composite guild diets could be explained by a suite of non-diet variables. All CAP models explained a significant proportion of the variance in the diet matrices, ranging from 7% to 25% of the total variation. Explanatory variables tested included latitude, longitude, predator length, depth, and water mass. These results indicate a trophic guild structure is present amongst the demersal fish community during summer in the eastern Chukchi Sea. Regular monitoring of the food habits of the demersal fish community will be required to improve our understanding of the spatial, temporal, and interannual variation in diet composition, and to improve our ability to identify and predict the impacts of climate change and commercial development on the structure and functioning of the Chukchi Sea ecosystem.